The influence of design factors on the financing results of crowdfunding projects: A focus on level setting and quality signaling. (13th August 2018) - Zhu, Cong; Li, Xingchen
Abstract : Purpose: The money raised for projects on crowdfunding platforms is determined not only by the merit of the projects themselves but also, to a large extent, by the design of the project introduction on the platforms. The purpose of this study is to identify the clear relationships between the financing result and the design factors to give preferable design suggestions to the fund initiators. Design/methodology/approach: The data for this study were abstracted with Python from the Jingdong crowdfunding platform on a certain day. In all, 11 hypotheses are put forward in the study with the two main purposes of exploring the function of the quality signaling and level setting. Findings: All design factors can impact the money raised for a project. However, the impact differs in certain situations. The level setting can significantly impact the amount of money raised. The quality of signals has a complex impact on the two dimensions. Originality/value: Three major contributions are made by this paper. First, the level setting is explored after overcoming the difficulty of scrawling data. Second, the authors create the Success Index and Weighted Gap Index to measure the level of success from comprehensive dimensions and quantify the dispersion of the levels. Third, this study shows a comprehensive theoretical framework which can function as a reference for research in the future.